Association of Menopausal Symptoms with Body Composition Pattern and Body Mass Index Across Menopausal Age Among Mongolian Women (Central Asian Journal of Medical Sciences, 2020)
Objectives: To investigate the correlation of body fat distribution pattern and body mass index (BMI) on the prevalence and clinical manifestation of menopausal symptoms across the menopausal stage among Mongolian women. Methods: A survey was conducted amongst a total of 1084 women aged 40-65 years Ulaanbaatar city and selected provinces representing five main remote regions of Mongolia. A questionnaire was used to collect demographic and socioeconomic data. Menopause related characteristics were evaluated using the Menopause-specific Quality of Life (MENQOL) questionnaire. Further, measurements were recorded to determine waist-to-hip-ratio and body mass index (BMI). Pearson's Chi-Square test was used to correlate. Results: Using the waist-to-hip-ratio, 84.4% of participants had the android type, and 15.6% were of the gynoid type. As for BMI, 38.4% were overweight, and 28.8% were obese. In multiple regression analysis, BMI had significant relationships with psychosocial and sexual problems (p